The speech acts and the communicative functions performed in thesis examinations: a pragmatic analysis - Susilawati, Endang (UPT Bahasa Universitas Tanjungpura, 2019)
Being a communicative event, a thesis examination process might generate a number of speech acts that possibly imply various meanings. To interpret meaning, a pragmatic analysis was implemented. The data analyzed comprised the authentic speech acts occurring within four thesis examination situations which were conducted by the EESP of FKIP Untan. The data analysis started by transcribing the speech recordings and by identifying the structures of the speech acts. This was followed by categorizing the communicative functions being performed. The last stage involved interpreting the contextual meaning of the speech acts. Three qualitative conclusions are arrived at in connection with and emerging from interpretations of the textual data: (1) the speech acts produced by the participants used various structures such as statements, questions, commands, instructions, prohibition and description; (2) the speech acts denoted various kinds of communicative or speech functions like expressives, directives, representatives, referentials, comissives, and metalinguistics; and (3) the occurrence of one particular communicative function can dynamically entail specific kinds of communicative functions in the light of the available context. Some categories of speech functions were not consistent with the purpose of the communicative event of thesis examination.